PENERAPAN MODEL USE QUESTIONNAIRE UNTUK MENGANALISIS USABILITY YANG DIPENGARUHI OLEH USER EXPERIENCE PADA APLIKASI SHOPEE - Mila Kartika Sari; Hario Jati Setyadi; Vina Zahrotun Kamila (SOTVI - Society of Visual Informatics, 2023)
E-commerce is defined as buying and selling transactions online through media in the form of the internet and internet-connected devices. Shopee is one of the most popular marketplace platforms chosen by the public in 2022 based on iPrice Group data. The usability aspect of the application needs to be considered to improve the user experience. Usability can affect the user experience during their use. This study aims to determine the effect of user experience on usability and to determine the factors that influence user satisfaction when using the Shopee application. One of the methods used in analyzing usability and user satisfaction is the Usage Questionnaire which has 4 measurement parameters namely Usability, Ease of Use, Ease of Learning, and Satisfaction. Data processing was carried out with usability measurements and the help of SmartPLS v4.0.8 software. Respondents in this study are active users of the Shopee application in Samarinda City, East Kalimantan. The results showed that the usefulness, ease of use, and ease of learning variables had a significant effect on user satisfaction and what affected the user experience at the usability level were the memoryability, learnability, and efficiency variables.